Hyper-Kamiokande construction status and prospects - Abe, Ko; Tanaka, Hide-Kazu (Frontiers in Physics, 2024)
The Hyper-Kamiokande (Hyper-K) project is the world's leading international neutrino and nucleon decay experiment comprising a next-generation underground water Cherenkov detector and upgraded Japan Proton Accelerator Research Complex (J-PARC) neutrino beam. It will provide an enormous potential to discover the leptonic charge-parity violation, to investigate the Grand Unified Theory by proton decay exploration, and to determine the neutrino mass ordering.Further, Hyper-K will significantly enhance the capability to observe solar neutrinos and neutrinos from other astronomical sources in comparison with its predecessors. After the budget approval in January 2020, the Hyper-K project officially began, and the operation is expected to start in 2027. The excavations of a 2.0 km long access tunnel and the tunnels for the detector facility have been completed. In October 2022 it was started the excavation of one of the world's largest underground caverns to suite the HK detector. This article discusses the status and the prospects of the Hyper-K detector construction.